Ferroelectric Copolymer-Based Plastic Memory Transistors - Yoon, Sung-Min; Yang, Shinhyuk; Jung, Soon-Won; Park, Sang-Hee Ko; Byun, Chun-Won; Ryu, Min-Ki; Oh, Himchan; Hwang, Chi-Sun; Cho, Kyoung-Ik; Yu, Byoung-Gon (IntechOpen, 2011)
None